2022
DOI: 10.4067/s1726-569x2022000100105
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Framework for Ethical Decision-Making During Public Health Emergencies

Abstract: The new theoretical ethical framework is a general frame or tool for ethical agents, developed to guide ethical reasoning during public health emergency preparedness and response. The TEF is based on the assumption that no existing ethical discourse in medical ethics alone is sufficient to address ethical issues of a PHE. The solutions suggested by existing approaches are limited in practicability and effectiveness, because they cannot address root problems and interplay among ethical problems. The reason for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(26 reference statements)
0
2
0
Order By: Relevance
“… 15 The work of Ekmekci and Folayan was influenced by the impacts of the coronavirus disease 2019/COVID-19 pandemic to improve decision-making practices; the proposed framework would benefit from evaluation and testing in the context of an all hazards approach. 16 Similarly, Knebel, et al proposed a decision-making process for government leadership in allocation of resources in disaster and developed a logic model utilizing a values-based framework. 17 A focused investigation of ethical decision making of EMS in Iran undertaken by Torabi, et al revealed themes of maintaining patient dignity and respect and regulation-based actions as key tenets guiding EMS decision making.…”
Section: Resultsmentioning
confidence: 99%
“… 15 The work of Ekmekci and Folayan was influenced by the impacts of the coronavirus disease 2019/COVID-19 pandemic to improve decision-making practices; the proposed framework would benefit from evaluation and testing in the context of an all hazards approach. 16 Similarly, Knebel, et al proposed a decision-making process for government leadership in allocation of resources in disaster and developed a logic model utilizing a values-based framework. 17 A focused investigation of ethical decision making of EMS in Iran undertaken by Torabi, et al revealed themes of maintaining patient dignity and respect and regulation-based actions as key tenets guiding EMS decision making.…”
Section: Resultsmentioning
confidence: 99%
“…Some scholars claim that the neutrality of moral agents and freedom from bias are unrealistic ideals that may make the CM theory less practical ( 11 ). When the CM theory is introduced to normative issues, problems with coherence and practicality arise because the CM theory ignores the role of the moral agent who interprets and applies the principles.…”
Section: Introductionmentioning
confidence: 99%
“…The wide reflective equilibrium approach facilitates the examination of the solutions to ethical problems by integrating basic ethical principles with the ethical paradigm of the context in which they arise; the role and competence of the moral agent are also effective in this approach. Some scholars claim that the neutrality of moral agents and freedom from bias are unrealistic ideals that may make the CM theory less practical (11).…”
Section: Introductionmentioning
confidence: 99%